The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2023
DOI: 10.1111/obr.13562
|View full text |Cite
|
Sign up to set email alerts
|

Overweight, obesity and risk of multimorbidity: A systematic review and meta‐analysis of longitudinal studies

Abstract: Summary This study aimed to review and quantify the association between overweight and obesity in the risk of multimorbidity among the general population. We conducted a systematic review and meta‐analysis in the databases of Pubmed, Lilacs, Web of Science, Scopus, and Embase. We included cohort studies that assessed the association between overweight and/or obesity with the risk of multimorbidity. The Newcastle‐Ottawa assessed the studies' individual quality. A random‐effect model meta‐analysis was performed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 43 publications
2
9
0
Order By: Relevance
“…
The missing piece: Why clinicians, epidemiologists, and policymakers need prediction intervals in a meta-analysis Delpino and colleagues have touched upon a very important topic in multiple long-term medical conditions-multimorbidity (MLTC-M). 1 Being overweight and having obesity leads to an elevated risk of developing MLTC-M (RR: 1.26, 1.12-1.40, I 2 of 98%; RR: 1.99, 1.45-2.72, I 2 of 99%) as reported by this systematic review and meta-analysis (SRMA).The authors have summarized the results from published studies.
…”
mentioning
confidence: 78%
See 1 more Smart Citation
“…
The missing piece: Why clinicians, epidemiologists, and policymakers need prediction intervals in a meta-analysis Delpino and colleagues have touched upon a very important topic in multiple long-term medical conditions-multimorbidity (MLTC-M). 1 Being overweight and having obesity leads to an elevated risk of developing MLTC-M (RR: 1.26, 1.12-1.40, I 2 of 98%; RR: 1.99, 1.45-2.72, I 2 of 99%) as reported by this systematic review and meta-analysis (SRMA).The authors have summarized the results from published studies.
…”
mentioning
confidence: 78%
“…2 of the study. 1 Since the analysis details were not given in a reproducible manner, we proceeded with the inverse variance method using the DerSimonian-Laird estimator for τ 2 . Our concerns were confirmed as the prediction intervals for the risk of MLTC-M crossed the risk ratio of one, both for obesity and overweight [0.81-4.72, 0.90-1.72, respectively].…”
mentioning
confidence: 99%
“…The association between adiposity and multimorbidity has been extensively explored in epidemiological studies [ 12 , 23 , 24 , 36 38 ]. For instance, a systematic review and meta-analysis of 8 longitudinal studies found a higher risk of multimorbidity among individuals with obesity [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…The association between adiposity and multimorbidity has been extensively explored in epidemiological studies [ 12 , 23 , 24 , 36 38 ]. For instance, a systematic review and meta-analysis of 8 longitudinal studies found a higher risk of multimorbidity among individuals with obesity [ 36 ]. Similarly, a cross-sectional study involving 20,198 participants from China, India, Ghana, Mexico, Russia and South Africa reported that significant positive association between obesity (measured by BMI and WC) and 5 out of 12 included chronic conditions [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Two recent systematic reviews focused on the prevalence of multimorbidity, 11 or analsed a single risk factor for multimorbidity development among subjects with overweight or obesity. 12 Other reviews generally focused on scoping older cross-sectional studies in one region (i.e., South Asia), 13 or solely considered non-communicable diseases (NCDs). 2,14 To our knowledge, none have focused on longitudinal investigations of determinants of multimorbidity consisting of both communicable and NCDs among the general populations in LMICs.…”
Section: Introductionmentioning
confidence: 99%